Model of Drug-Loaded Fluorocarbon-Based Micelles Studied by Electron-Spin Induced 19F Relaxation NMR and Molecular Dynamics Simulation - Mathias, Errol V; Liu, Xiangli; Franco, Osmundo; Khan, Imran; Ba, Yong; Kornfield, Julia A (Langmuir, 2008)
R f-IPDU-PEGs belong to a class of fluoroalkyl-ended poly(ethylene glycol) polymers (R f-PEGs), where the IPDU (isophorone diurethane) functions as a linker to connect each end of the PEG chain to a fluoroalkyl group. The R f-IPDU-PEGs form hydrogels in water with favorable sol−gel coexistence properties. Thus, they are promising for use as drug delivery agents. In this study, we introduce an electron-spin induced 19F relaxation NMR technique to probe the location and drug-loading capacity for an electron-spin labeled hydrophobic drug, CT (chlorambucil-tempol adduct), enclosed in the R f-IPDU-PEG micelle. With the assistance of molecular dynamics simulations, a clear idea regarding the structures of the R f-IPDU-PEG micelle and its CT-loaded micelle was revealed. The significance of this research lies in the finding that the hydrophobic drug molecules were loaded within the intermediate IPDU shells of the R f-IPDU-PEG micelles. The molecular structures of IPDU and that of CT are favorably comparable. Consequently, it appears that this study opens a window to modify the linker between the R f group and the PEG chain for achieving customized structure-based drug-loading capabilities for these hydrogels, while the advantage of the strong affinity among the R f groups to hold individual micelles together and to interconnect the micellar network is still retained in hopes of maintaining the sol−gel coexistence of the R f-PEGs.